ANALISIS KESALAHAN MENGERJAKAN SOAL MATEMATIKA MATERI PECAHAN DENGAN TEORI NEWMAN - Fian Yulia Nur Fatimah (As-Sibyan, 2018)
Schools are a service group that organizes education on formal, non-formal, and informal channels at every level and type of education. Mathematics is one of the compulsory subjects that is used as a school exam or graduation exam at the elementary school level. The low ability to count students in working on math problems can be seen from the results of the midterm. The first step to overcome this problem is to look for mistakes made by fifth grade students in working on mathematical problems with fractions. Qualitative data analysis is used in research to produce descriptive data in the form of written or oral words from people and observable behavior, so that it uses a qualitative approach. This study aims to describe the mistakes of students in working on fraction material math problems with Newman's theory. The research was carried out in two Ibtidaiyah Madrasas in the sub-district of Semin, Gunungkidul in March 2017. April 2017. Data collection techniques are carried out using the method of observation, documentation and interviews. Data is analyzed by data reduction, data presentation and conclusion drawing.The results of the research conducted were 1) errors made by students in working on math problems were reading errors; mistake of understanding; transformation error; process skill errors; and errors in the final answer. The most dominant mistake made is a mistake to understand. The total errors made by students in working on mathematical questions from 15 questions and 31 student work documents were three times reading errors; misunderstanding 261 times; 131 times transformation error; error in processing skills 20 times; and the final answer error 14 times.